Legal Accountability for Malpractice in Pet Ownership: A Case Study of Pet Shops - Afandy Hermawan, Mohamad; Puluhulawa, Fenty U.; Mamu, Karlin Z. (Estudiante Law Journal, 2025)
The phenomenon of violence against pets is increasingly prevalent in Indonesia, including malpractice committed by pet shops that provide medical services without proper authorization. This study aims to analyze the criminal legal liability for pet malpractice by pet shops and to identify the inhibiting factors in law enforcement in Gorontalo City. The research adopts a normative-empirical approach through a two-month field study using purposive sampling techniques involving cat lover communities, victims, and the police. Primary data were obtained through interviews and observations, while secondary data were collected through literature studies. The discussion highlights the case of Liga Pet Shop, which performed tail docking and administered restricted drugs without authorization—acts that fulfilled the elements of actus reus and mens rea, violating Article 302 of the Indonesian Criminal Code (KUHP) and Law No. 41 of 2014 on Animal Husbandry and Animal Health. However, criminal liability was not strictly enforced and concluded only with an apology. Inhibiting factors include weak specific regulations, limited competence of animal forensic officers, lack of investigative facilities, low public legal awareness, and a permissive culture in dispute resolution. The proposed recommendations include strengthening regulations by establishing standard operating procedures (SOPs) for pet shops, enhancing officer competence through animal forensic training, providing adequate investigative infrastructure, and launching public legal awareness campaigns. The study concludes that reforming the animal legal protection system is necessary through an integrative approach combining repressive, educational, and preventive measures to achieve fair and effective law enforcement